Educational and motivational support service: a pilot study for mobile‐phone‐based interventions in patients with psoriasis. (13th December 2012) - Balato, N.; Megna, M.; Di Costanzo, L.; Balato, A.; Ayala, F.
Summary: Background Psoriasis is a chronic disease which requires long‐term therapy. Therefore, adherence to therapy and patient motivation are key points in controlling the disease. Mobile‐phone‐based interventions, and in particular text messages (TM), have already been used effectively to motivate patients and improve treatment adherence in many different chronic diseases such as diabetes, cardiovascular disease and asthma. Objectives To evaluate the use of TM in improving treatment adherence and several patient outcomes such as quality of life, disease severity, patient‐perceived disease severity and the patient–physician relationship. Patients and methods Daily TM, providing reminders and educational tools, were sent for 12 weeks to a group of 20 patients with psoriasis. At the beginning and end of the study the following assessments were performed: Psoriasis Area Severity Index (PASI), Self‐Administered Psoriasis Area Severity Index (SAPASI), body surface area (BSA), Physician Global Assessment (PGA), Dermatology Life Quality Index (DLQI), evaluation of patient–physician relationship and adherence to therapy. A matched control group of 20 patients with psoriasis was used for comparison of the same outcomes. Results Both patient groups had similar scores for PASI, SAPASI, BSA, PGA and DLQI at baseline. However, after 12 weeks the intervention group reported a significantly better improvement of disease severity as well as quality of life, showing lower values of PASI, SAPASI, BSA, PGA and DLQI with respect to the control group ( P < 0·05). Moreover, adherence to therapy improved in a statistically significant way ( P < 0·001) whereas it remained stable in the control group. Similarly, TM interventions led to an optimization of patient–physician communication. Conclusions TM interventions seem to be a very promising tool for the long‐term management of patients with psoriasis, leading to an increased compliance to therapy, positive changes in self‐care behaviours and better patient–physician relationship allowing improved clinical outcomes and better control of the disease.